Digital Literacy for Rural Teachers Through Optimization of Learning Applications to Support the Implementation of the Kurikulum Merdeka - Syafruddin, Syafruddin; Aprianto, Romi; Safitri, Ade (Pascasarjana Universitas Mataram, 2025)
This community service initiative focuses on enhancing digital literacy among teachers at SDN Semongkat, Sumbawa Regency, in an effort to support the implementation of the Merdeka Curriculum in remote areas. The program was executed through a series of workshops and intensive mentoring sessions on the utilization of learning applications such as Canva, Google Classroom, Quizizz, and Kahoot. The implementation method comprised three main stages: preparation, execution (consisting of socialization, training, and mentoring), and evaluation. The outcomes of the service demonstrated a significant improvement in teachers' abilities to use and integrate digital applications into their teaching practices. The primary challenge of infrastructure limitations was addressed through adaptive learning strategies. This program successfully enhanced the quality of learning at SDN Semongkat and fostered a digital-based professional learning community among teachers. This community service initiative made a tangible contribution to bridging the digital divide in remote areas and effectively supporting the implementation of the Merdeka Curriculum.